EFEKTIVITAS EMBARGO DALAM MENDORONG DEMOKRATISASI DI MYANMAR - Pramono, Sugiarto (Forum Ilmu Sosial, 2014)
International pressure on the junta in Myanmar (in particular the American, UN and Europe embargo) becomes positive signal to the democracy movement in the country, although effective or not is still questionable. Not to mention the matter is completed, the pessimism of development of democracy in Myanmar is reinforced by the approach of two new giant in th world economy (India and China); and "naughty child", North Korea. As two country with high economic growth, energy needs can not be Words: Embargo, effectiveness postponed. energy Interests of the two giant meets the Myanmar interests that one side has abundant energy resources such as natural gas and petroleum, but on the other hand require political support from India and China because of international pressure. And, the argument of realist "enemies enemy is a friend" has encourage North Korea to supply nuclear technology to Myanmar. In addition to these international factors, this study also found a number of patterns associated with the involvement of China, India and North Korea in the failure of the embargo: (1) distribution of the power of the global political economy has become more complex. USA, EU and the UN are not longer a global actors uncontested, the rise of the Asian giants seem to weaken if reluctant to say: terminate their domination; (2) the pattern of change in the political-economic power shift from the previous one in the west (America and Europe) moved to the east (India and China); and (3) changes in the pattern would seem to open the possibility of changing of the behavior of third world countries who are seen, one of which is Myanmar's behavior.